Parotid Gland Enlargement: A Diagnostic Challenge - Shaik, Shabana; Patil, Bharati; Jain, Lishika (Archives of Clinical and Medical Case Reports, 2025)
Parotid swelling may develop secondary to infections or systemic disorders such as diabetes mellitus. This report describes a 51 year old man presenting with Recurrent Parotitis associated with inadequate glycaemic control. Diagnosis was established through clinical examination, imaging and laboratory investigations. Therapy consisted of broad spectrum antibiotics, supportive measures and improved blood sugar management, leading to a marked recovery. This case illustrates how systemic disease can influence salivary gland pathology and stresses the need for multidisciplinary care for long term success.